Investigation of the possibility of shaping an electron dose field of a clinical accelerator with 3D printed polymer products; Nuclear Instruments and Methods in Physics Research Section A: Accelerators, Spectrometers, Detectors and Associated Equipment; Vol. 1059 - Miloichikova I. A. Irina Alekseevna; Bulavskaya A. A. Angelina Aleksandrovna; Gargioni E. Elisabetta; Grigorieva (Grigorjeva) A. A. Anna Anatoljevna; Cherepennikov Yu. M. Yuriy Mihaylovich; Belousov D.; Stuchebrov S. G. Sergey Gennadevich (2024, 2024)
Title screen